Yeast peptides alleviate diarrhea in neonatal lambs by enhancing the colonic barrier function and modulating colonic microbiota - Fan, Dingkun; Zong, Rui; Zhang, Chengrui; Zhang, Jixian; Chai, Jianmin; Cui, Kai; Zhang, Naifeng (Frontiers in Veterinary Science, 2025)
The underdeveloped intestinal tissue and immature microbiota in neonatal lambs predispose to frequent diarrhea or even death, expanding the breeding losses. Yeast peptides are enzymatic products of yeast strains, recognized as antimicrobial peptides due to their demonstrated antimicrobial properties. This study aimed to investigate the impacts of yeast peptides supplementation on the incidence of diarrhea in neonatal lambs, as well as the underlying regulatory mechanisms involved. Thirty-two one-day-old lambs were randomly allocated to four treatments: CON, YP500, YP1000, and YP2000, receiving 0 mg/d, 500 mg/d, 1,000 mg/d, and 2,000 mg/d of yeast peptides, respectively. The dietary supplementation of yeast peptides elicited a significant reduction in fecal scores and the incidence of diarrhea (p < 0.05). The administration of yeast peptides to neonatal lambs markedly elevated the levels of anti-inflammatory factors (IL-4, IL-10) while concurrently suppressing the levels of pro-inflammatory factors (IL-1β, IL-6) in the colonic mucosa (p < 0.05). Furthermore, yeast peptides enhanced intestinal antioxidant capacity and ultimately strengthened colonic barrier function (p < 0.05). Supplementation with yeast peptides altered the colonic microbiota of lambs, characterized by a marked increase in Roseburia and a decrease in Staphylococcus and Escherichia_Shigella abundances. Correlation analysis revealed that the observed attenuation in inflammatory response and enhancement of barrier function were associated with the enrichment of Roseburia and the suppression of Staphylococcus and Escherichia_Shigella. In conclusion, yeast peptides demonstrate potential in ameliorating diarrhea of lambs through the modulation of microbial communities and the enhancement of barrier function in the colon of lambs. The recommended dosage of yeast peptides is 2,000 mg/d.